2017
DOI: 10.5430/wje.v7n4p12
|View full text |Cite
|
Sign up to set email alerts
|

Gender Dimension in the Development of Effective Teaching Skills among University of Cape Coast (Ucc) Distance Education Students

Abstract: The study examined gender dimension in the development of effective teaching skills among distance education (DE) students. The conceptual framework for the study is gender mainstreaming which centres on pluralistic approach to diversity issues among both men and women. A longitudinal developmental research design was used for the study. A sample size of 376 distance education students made up of 173(46.01%) female and 203 (53.99%) male were purposefully selected from 5 regional study centres of College of Dis… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
3
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 15 publications
1
3
1
Order By: Relevance
“…It could further indicate that being a male or a female does not play a substantial role in determining the knowledge and skills acquired as it highlights the need for equal opportunities and recognition for the acquisition of PGT. This result differs from previous research who found that females performed better than their male counterparts in terms of the teaching skills acquired during internship (Adu-Marfo et al, 2024;Ahiatrogah, 2017). The other study also observed a small difference in how male and female interns assessed their skill development (Ang, 2015;Monogaran & Subramaniam, 2023).…”
Section: Discussioncontrasting
confidence: 86%
“…It could further indicate that being a male or a female does not play a substantial role in determining the knowledge and skills acquired as it highlights the need for equal opportunities and recognition for the acquisition of PGT. This result differs from previous research who found that females performed better than their male counterparts in terms of the teaching skills acquired during internship (Adu-Marfo et al, 2024;Ahiatrogah, 2017). The other study also observed a small difference in how male and female interns assessed their skill development (Ang, 2015;Monogaran & Subramaniam, 2023).…”
Section: Discussioncontrasting
confidence: 86%
“…Thus, the training is expected to produce student teachers with effective teaching skills, good personal and affective characteristics irrespective of gender. This is in agreement with (Ahiatrogah, 2017), who examined gender dimension in the development of effective teaching skills among distance education (DE) students and found out that there was no statistically significant difference between the teaching skills acquired by male and female students during On-Centre-Teaching-Practice. Further, teaching practice schools are chosen so that every school has sufficient resources and learning environment to enable teachers carry out their practicum.…”
Section: Figure 1 Conceptual Framework Of the Study Showing How Varisupporting
confidence: 88%
“…The initial training received by teachers leads to the entry qualification into the teaching profession (Ahiatrogah, 2017). Teachers' beliefs and interest in the OT mode are usually shaped by their experience of their teacher education programme (Varol, 2013).…”
Section: Relationship Between Teachers' Academic Qualifications and T...mentioning
confidence: 99%